Praktik Pengabdian Masyarakat Melalui Edukasi Pencegahan Stunting di Desa Kanje Campalagian Polewali Mandar Sulawesi Barat - Syamsuri Syamsuri; Hafsah Hafsah; Hasria Alang; Ahmad Hasyim; Muh. Yunus (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2023)
This PKM activity aims to increase the knowledge and awareness of PKK women and Posyandu cadres in Kanje Campalaian Village regarding the dangers and efforts to prevent stunting. The method of implementing this service used health promotion based on community education. Evaluation instruments were pretest, posttest, and activeness when the activity took place. The analytical technique to determine the activity's success was by comparing the results of the pre-test and post-test that have been given. The service results showed an increase in the knowledge of PKK mothers and posyandu cadres regarding matters related to stunting, from 57% to 80%. Some of the materials that partners understood include the characteristics of stunting, the causes of stunting in relation to nutrition, and the long-term impacts caused by stunting cases. It means that the implications of this PKM activity have increased partners' knowledge and understanding.